Analisis Produktivitas Alat Berat dan Pekerja di Pekerjaan Pengecoran Lantai Spillway pada Proyek Pembangunan Bendungan - Mery Komalasari; Dinda Fardila; Dedy Dharmawansyah; Eti Kurniati (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2023)
Productivity is one of the keys to determining the factors that affect competitiveness in construction projects, including the productivity of workers and heavy equipment for spillway casting work at Dam Development. The aim of the research is to analyze productivity and factors affecting heavy equipment and workers. This research using quantitative descriptive calculation methods, and observation in field time study. The results of the data calculations show that the productivity value of a concrete pump is 167.491 m3/day, the productivity of mixer trucks is 46.305 m3/day/unit, and the productivity of workers is 13.790 m3/day/person. Factors that affect heavy equipment productivity are weather, work time efficiency, and material or payload. As well as factors that affect worker productivity, there are the weather, worker time efficiency, foundry location, and the number of workers.